Six Sigma-Based Quality Management Strategy to Enhance the Competitiveness of Food Souvenir MSMEs in East Kalimantan - Kisanjani, Alex; Andivas, Marulan; Hirwandi, Hirwandi (Spektrum Industri, 2026)
Micro, Small, and Medium Enterprises (MSMEs) plays an important role in the Indonesian economy. MSMEs contribute around 60% to the Gross Domestic Product (GDP) and absorb more than 97% of the workforce. The culinary sector, especially local specialty culinary products, is one of the fastest-growing sectors and has great potential to boost the local economy, including in East Kalimantan. However, this potential is not fully realized because many MSMEs still face issues with product quality. This condition reduces MSMEs' market competitiveness. This research aims to develop a strategy to improve MSME quality by prioritizing key areas. The method used is Six Sigma, with the stages of Define, Measure, Analyze, Improve, and Control (DMAIC), combined with Importance-Performance Analysis (IPA). Data collection is conducted through a customer satisfaction questionnaire, which is then analyzed using Six Sigma methods to determine performance levels. The findings indicate that the sigma level of food souvenir MSMEs in East Kalimantan is 2.435. This figure suggests that the process capability in meeting customer expectations remains low. The Importance-Performance Analysis (IPA) identified three priority attributes for improvement: staff appearance, communication with customers, and the provision of product testers. The proposed improvement recommendations are complemented by Key Performance Indicators (KPIs) to ensure the sustainability of quality enhancement efforts. The novelty of this study lies in applying the Six Sigma method to small-scale culinary MSMEs through a multidimensional approach that integrates product quality, service quality, pricing, and customer experience within the context of a developing region. In practice, this study contributes to offer measurable improvement priorities for MSME practitioners, thereby supporting the enhancement of MSME competitiveness at both the local and national levels.